1990
DOI: 10.1128/mcb.10.8.3987
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between distinct enhanson domains in viral induction of the human beta interferon gene.

Abstract: This study demonstrates distinct virus-inducible enhanson properties for three regions of the human beta interferon (IFN-,B) promoter; maximum vrus inducibility required syngerism among all three enhansons. Expression of the ERF-1 transcription factor differentially increased the expression of plasmids containing (AAGTGA)4 or PRDM (-94 to -78) motifs but was inefficient in the induction of the intact IFN-0 promoter.The human T-cell (11,14,38,41). The contribution of an individual enhanson to overall enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 51 publications
3
60
0
1
Order By: Relevance
“…No detectable production of IFN-f in RI cells after IFN treatment was in agreement with results in stable transfectants overexpressing IRF-1 derived from other cell types (Leblanc et al, 1990;Reis et al, 1992). Under viral induction, RI and R2 cells produced 2.46-and 2.24-fold higher IFN-f than C-76 cells, and under poly(I): poly(C) stimulation after IFN-P priming, RI and R2 cells produced 2.33-and 1.87-fold higher IFN-P than C-76 cells respectively (Table 1).…”
Section: Ifn-p Production and Expression Of Ifn-b Gene In Rl And R2 supporting
confidence: 75%
“…No detectable production of IFN-f in RI cells after IFN treatment was in agreement with results in stable transfectants overexpressing IRF-1 derived from other cell types (Leblanc et al, 1990;Reis et al, 1992). Under viral induction, RI and R2 cells produced 2.46-and 2.24-fold higher IFN-f than C-76 cells, and under poly(I): poly(C) stimulation after IFN-P priming, RI and R2 cells produced 2.33-and 1.87-fold higher IFN-P than C-76 cells respectively (Table 1).…”
Section: Ifn-p Production and Expression Of Ifn-b Gene In Rl And R2 supporting
confidence: 75%
“…6D). Thus, the transcription factors that are responsible for inducible activ- (7,11,39). The combination of these elements in the HuIFN-,Bpromoter…”
Section: Resultsmentioning
confidence: 99%
“…The positive regulatory domain I (PRDI) is located between nucleotides -77 and -64 from the start site of transcription, while another element (PRDII) is located between -66 and -55 (7)(8)(9)(10). A third element (PRDIII) is located between -90 and -78 (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…This finding is consistent with other observations showing that overexpressed IRF-1 can superinduce target gene expression induced by exogenous stimuli. Leblanc et al (35) demonstrated that IRF-1 could superinduce phorbol ester-mediated activation of an IFN-␤ promoter/reporter construct. Reis et al (58) studied cells stably overexpressing IRF-1 and observed superinduced levels of endogenous IFN-␤ when transfected cells were stimulated by either poly(I)-poly(C) or virus.…”
Section: Discussionmentioning
confidence: 99%
“…Full-length cDNAs encoding p50, HMGI, and IRF-1 were cloned in frame to glutathione S-transferase (GST)-expressing plasmids (13). GST alone or its fusion derivatives immobilized to glutathione-agarose beads were incubated with in vitro-translated 35 S-labeled proteins for 2 h at 4ЊC in binding buffer (150 mM NaCl, 10 mM Tris [pH 8.0], 0.2% Nonidet P-40, 0.2% BSA) and then washed three times with binding buffer and once with binding buffer but without BSA. Interactions were analyzed by SDS-polyacrylamide gel electrophoresis (PAGE).…”
Section: Methodsmentioning
confidence: 99%